1996
DOI: 10.1007/bf00123912
|View full text |Cite
|
Sign up to set email alerts
|

An object-oriented bill of materials system for dynamic product management

Abstract: In this paper, the bill of materials (BOM) system is defined as the central hub of a general product data management (PDM) system that provides essential data for running a manufacturing system to produce products. Information that is relevant to products and their components is defined in the BOM. The information is critically related to data from product design, manufacturing planning, production management, procurement, inventory control, and accounting within a company. A conventional BOM structure (or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…In practice, the PS can encompass various data types -such as specification documents or geometric representations of a given part -as shown in the example of the multi-view PS shown in Figure 5. Trappey et al (1996) identified at least ten major data types and functions including product definition, service parts support, material purchase planning, assembly sequence, order entry facility, resource analysis, pricing, cost analysis, manufacturing instruction and engineering change control. For product design and manufacturing management purposes, PLM systems offer, in addition to the PS manager, a workflow engine which "according to the product structure, sends the right available data at the right time to the right user" (Eynard et al, 2004).…”
Section: Definition Of Conceptsmentioning
confidence: 99%
“…In practice, the PS can encompass various data types -such as specification documents or geometric representations of a given part -as shown in the example of the multi-view PS shown in Figure 5. Trappey et al (1996) identified at least ten major data types and functions including product definition, service parts support, material purchase planning, assembly sequence, order entry facility, resource analysis, pricing, cost analysis, manufacturing instruction and engineering change control. For product design and manufacturing management purposes, PLM systems offer, in addition to the PS manager, a workflow engine which "according to the product structure, sends the right available data at the right time to the right user" (Eynard et al, 2004).…”
Section: Definition Of Conceptsmentioning
confidence: 99%
“…Por compartilhar suas informações entre quase todos os departamentos da empresa, a BOM ainda funciona como um importante elemento de integração dos sistemas de manufatura adotados (TRAPPEY et al, 1996).…”
Section: Lista De Materiaisunclassified
“…In practice the Product Structure can encompass various data types. Trappey et al [24] identified at least 10 major data types and functions including product definition, service parts support, material purchase planning, assembly sequence, order entry facility, resource analysis, pricing, cost analysis, manufacturing instruction, and engineering change control. For product design and manufacturing management purposes, PLM systems require, in addition to the product structure manager, a workflow engine which "according to the product structure, sends the right available data at the right time to the right user" [23].…”
Section: What Is It?mentioning
confidence: 99%